The Gift of Logos. The Life of Aesop and Socrates’ Poetic Initiation - Capra, Andrea (Giornale Italiano di Filologia, 2019)
Abstract This paper explores a crucial, if neglected, point of comparison between Plato’s Socrates and the Life of Aesop, namely their shared relationship with the Greek tradition of poetic initiations. The combined study of how Socrates and Aesop fit into that tradition provides an invaluable vantage point to explore the generic boundaries of Socratic dialogues and Aesopic fables. Aesop’s initiation as described in version G of the Life, with its emphasis on Aesop’s newly acquired ability to speak, proves crucially connected with a defining feature of Aesopic fables, namely the major role of speaking animals. Moreover, the scene closely recalls a number of passages in Plato’s dialogues, in which Socrates echoes the Dichterweihe tradition in terms of both poetic inspiration resulting in the ‘invention’ of dialogue and conversion to writing. Combined together, the passages under examination from Plato and from the Life amount to a literary manifesto pointing to the canonisation of prose genres, revolving, respectively, around the gift of logos and dialogos. They also suggest that an early and version of the Life might have provided Plato a foil to emphasise Socrates’ Apollonian piety in opposition to Aesop’s impiety in the Life. Abstract Il saggio prende in esame un parallelo, cruciale quanto inesplorato, fra il Socrate platonico e la Vita di Esopo, ossia la comune appartenenza alla tradizione greca delle iniziazioni poetiche. Uno studio in parallelo di come Socrate ed Esopo si pongono rispetto a tale tradizione offre un punto d’osservazione privilegiato per indagare i generi del dialogo e della favola e i loro confini. L’iniziazione di Esopo tramandata nella versione G della Vita insiste sul dono della parola che permette a Esopo di parlare, e si dimostra così intimamente connessa con un tratto distintivo della favola, popolata da animali parlanti. Inoltre, la scena richiama da vicino alcuni passi platonici nei quali Socrate si colloca nel solco della Dichterweihe in termini di ispirazione poetica, che conduce all’‘invenzione’ del dialogo, e di conversione alla scrittura. Presi congiuntamente in esame, i passi di Platone e della Vita costituiscono una sorta di manifesto letterario che ha per oggetto la canonizzazione dei generi in prosa, centrati rispettivamente su logos e dialogos. Questi passi suggeriscono inoltre che una versione antica della Vita possa aver offerto a Platone uno sfondo di contrasto per mettere in luce la pietà apollinea di Socrate in opposizione all’empietà di Esopo nella Vita.